(untitled) (Hematology Meeting Reports, 2009)
The regression of gastric MALT lymphoma after antibiotic eradication of H. pylori was first reported in 1993 by Wotherspoon and colleagues, who described the efficacy of antibiotic therapy in six patients with superficially invasive gastric MALT lymphoma.1 Our and other groups thereafter confirmed the efficacy of antibiotics in inducing apparently durable lymphoma remissions: in 60-100% of patients with localized H. pylori-positive gastric MALT lymphoma.2-9 The histologic remission can usually be documented within 6 months from the H. pylori eradication but sometimes the period required is more prolonged and the therapeutic response may be delayed up to more than 1 year.10